2002
DOI: 10.1128/jvi.76.7.3168-3178.2002
|View full text |Cite
|
Sign up to set email alerts
|

Open Reading Frame 50 Protein of Kaposi's Sarcoma-Associated Herpesvirus Directly Activates the Viral PAN and K12 Genes by Binding to Related Response Elements

Abstract: Open reading frame (ORF) 50 protein is capable of activating the entire lytic cycle of Kaposi's sarcomaassociated herpesvirus (KSHV), but its mechanism of action is not well characterized. Here we demonstrate that ORF 50 protein activates two KSHV lytic cycle genes, PAN (polyadenylated nuclear RNA) and K12, by binding to closely related response elements located approximately 60 to 100 nucleotides (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
158
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(159 citation statements)
references
References 42 publications
1
158
0
Order By: Relevance
“…Lytic infection is marked by the production of infectious virus, whereas latency is characterized by the lack of infectious virus production and the expression of a limited number of viral transcripts and proteins. One of the most abundant transcripts present in KSHV-infected cells is a long noncoding RNA, referred to as polyadenylated nuclear RNA (PAN RNA) (3,4).…”
mentioning
confidence: 99%
“…Lytic infection is marked by the production of infectious virus, whereas latency is characterized by the lack of infectious virus production and the expression of a limited number of viral transcripts and proteins. One of the most abundant transcripts present in KSHV-infected cells is a long noncoding RNA, referred to as polyadenylated nuclear RNA (PAN RNA) (3,4).…”
mentioning
confidence: 99%
“…Using similar methods Chang et al (2002) showed that the 490 aa RDBD was required for recognition and lytic activation of the PANp or the promoter for K12, another gene whose expression is upregulated in the lytic cycle. This activation was also evident when the RTAresponsive sequence was fused to the heterologous adenovirus E4 promoter demonstrating that RTA activation was dependent upon the RRE but independent of binding sites for cellular transcription factors that were distinct between PANp and the E4 promoter.…”
Section: Rta Interacts With Various Promoters and Factors To Mediate mentioning
confidence: 99%
“…A region of the PANp corresponding to nucleotides À70 to À46 [numbering according to Chang et al (2002)] was found to be essential to RTA activation of PAN expression. The K d of the RTA association with PANp has been reported to be in the nanomolar range (Song et al, 2001(Song et al, , 2002, suggesting that the high affinity of RTA for the PANp is likely responsible, in part, for the abundance of PAN RNA in cells expressing lytic transcripts.…”
Section: Rta Interacts With Various Promoters and Factors To Mediate mentioning
confidence: 99%
See 2 more Smart Citations